Karakteristik Konsumen dan Faktor-Faktor Yang Mempengaruhinya Dalam Pengambilan Keputusan Pembelian Sayuran di Total Buah Segar Summarecon Bekasi - Resha Maharani; Slamet Abadi; Suhaeni Suhaeni (Jurnal Ilmiah Wahana Pendidikan, 2022)
Trade in agricultural products in the field of horiculture, especially vegetables, is growing rapidly along with the increase in people's welfare. The stages in decision making are influenced by social, personal, cultural, and psychological factors. The diversity of backgrounds of each consumen with different culture, behavior, needs and desires, motivation makes information about consumen behavior increasingly needed by business actors to be able to compete to win the market. This study aims to analyze the characteristics of consumen and see the influence of cultural, social, personal, and psychological factors partially and simultaneously and find out the most dominant variables that influence vegetable purchasing decisions at Total Buah Segar Summarecon Bekasi. The sample is determined by using the unknown population formula, sampling using the accidental sampling method. The analytical technique used is multiple linear regression analysis, MSI, classical assumption test and hypothesis testing. The results of the study show that consumers are dominated by women as much as 89% with an average age of 34,03 years, the latest education level is dominated by bachelor's degrees as much as 40%, work as private employees with an average income level of Rp. 5,730,000, the number of dependents is 3 dependents. Hypothesis testing shows that the cultural, social, personal, psychological variables together have a significant effect on vegetable purchasing decisions. Cultural, personal and psychological variables have a significant effect partially and cultural variables are the most dominant in influencing vegetable purchasing decisions at Total Buah Segar Summarecon Bekasi